TINJAUAN HISTORIS MASYARAKAT MINANGKABAU DIDESA PASAR SORKAM (1939-1963) - diva yulanda (Jurnal TAROMBO, 2019)
Abstract This study aims to describe the existence of Minangkabau community at Pasar Sorkam village (1939-1963). The approach of the research was descriptive qualitative by applying history method which includes heuristic, source critic, interpretation, and historiography. Interview was used in collecting the data and the finding of the research were (1) Minangkabau community move to Pasar Sorkam in search of a better life, 2) the social relation of Minangkabau community at Pasar Sorkam village was very good because Minangkabau community involved in community activities at Pasar Sorkam (mutual cooperation), and 3) displacement pattern of Minangkabau community to Pasar Sorkam village was gradually. Keywords: historical review, community, Minagkabau, 1939-1963